PENGARUH FAMILY OWNERSHIP, KUALITAS AUDIT, DEWAN KOMISARIS, KOMITE AUDIT DAN RANGKAP JABATAN TERRHADAP MANAJEMEN LABA PERUSAHAAN DI INDONESIA - zulkarnaen, have; Hwihanus, Hwihanus; Riyadi, Slamet (Pro-fit, 2024)
Abstract Indonesia is estimated to have approximately 90% family companies. Family companies are seen from the existence of Family Ownership. Agency theory regulates companies, with capital owners and managers bound by contracts. However, when multiple families have ownership of a company, it is difficult to differentiate family interests from company interests. In addition, minority shareholders and controlling shareholders can be involved in conflicts of interest, one of which is earnings management in financial statements. Internal and external efforts can reduce earnings management efforts. This study tries to determine whether earnings management is influenced by family ownership, audit quality, board of commissioners, audit committee, and multiple positions. This research involved 70 companies running from 2021 to 2022, with 140 BEI data obtained through a purposive sampling method. Panel data regression models are used for estimation. There is a development model used to test the hypothesis used in this research, and the results are as follows. The first model shows that family ownership does not have a significant effect but has a positive impact on the earnings management of manufacturing companies listed on the IDX in 2021-2022. This model also shows that the proportion of independent boards has a negative impact on the earnings management of manufacturing companies listed on the IDX in 2021-2022. Keywords: Family Company, Company Efforts, Profit Management